The role, importance and role of ecotourism in the development of the state in foreign countries (Texas Journal of Philology, Culture and History, 2023)
this article cites information on the role, importance and role of ecotourism in the development of the state in foreign countries, models of use of national parks in the development of ecotourism and recreational tourism, American model, European model, park reservation model, Asian model and Australian models